Identification of Expressed Resistance Gene Analogs from Peanut (Arachis hypogaea L.) Expressed Sequence Tags23. Issue 5 (18th March 2013) - Liu, Zhanji; Feng, Suping; Pandey, Manish K.; Chen, Xiaoping; Culbreath, Albert K.; Varshney, Rajeev K.; Guo, Baozhu
Abstract Low genetic diversity makes peanut (Arachis hypogaea L.) very vulnerable to plant pathogens, causing severe yield loss and reduced seed quality. Several hundred partial genomic DNA sequences as nucleotide‐binding‐site leucine‐rich repeat (NBS‐LRR) resistance genes (R) have been identified, but a small portion with expressed transcripts has been found. We aimed to identify resistance gene analogs (RGAs) from peanut expressed sequence tags (ESTs) and to develop polymorphic markers. The protein sequences of 54 known R genes were used to identify homologs from peanut ESTs from public databases. A total of 1, 053 ESTs corresponding to six different classes of known R genes were recovered, and assembled 156 contigs and 229 singletons as peanut‐expressed RGAs. There were 69 that encoded for NBS‐LRR proteins, 191 that encoded for protein kinases, 82 that encoded for LRR‐PK/transmembrane proteins, 28 that encoded for Toxin reductases, 11 that encoded for LRR‐domain containing proteins and four that encoded for TM‐domain containing proteins. Twenty‐eight simple sequence repeats (SSRs) were identified from 25 peanut expressed RGAs. One SSR polymorphic marker (RGA121) was identified. Two polymerase chain reaction‐based markers (Ahsw‐1 and Ahsw‐2) developed from RGA013 were homologous to the Tomato Spotted Wilt Virus (TSWV) resistance gene. All three markers were mapped on the same linkage group AhIV. These expressed RGAs are the source for RGA‐tagged marker development and identification of peanut resistance genes.